Bentuk Clustering Pengembangan Kawasan Wisata Malino - Agus; Mardhatillah; Faisal; Goeltom, Andar Danova L; Muh Yahya; Muh Kasim (Politeknik Pariwisata NHI Bandung, 2021)
Planning as a system that can bring the suitable instruction to take the steps needed in developing tourism area. Through location clustering in one area based on the designation of facilities, amenities and accessibility. The Clustering concept is one of the concept that can be used in selecting and utilizing the location of tourism development in an area. Malino, as an area that has tourist attraction potential become attractiveness for the growth of the tourism business requires the right cluster design. This study used a qualitative approach with a descriptive exposure system and data collection technique by using Interview, observation and literature study. The analysis technique used were emperical and theoretical descriptive analysis. Furthermore, used clustering analysis to determine the map of Malino Tourism area. The result of this study indicates that, the basis on the formation of Malino tourism area cluster consists of: geographic proximity, connecting road conditions and differentiation of tourist attractions, resulting in the attractiveness cluster of the Malino tourist area consisting of water clusters, natural clusters, artificial clusters and agro tourism clusters.